Utilization of Anaerobic Co-Digestion for Biogas Production for Institutional Cooking: A Case of Nkumbi International College - Tembo Costain; Luwaya Edwin (Engineering And Technology Journal, 2024)
Studies have linked the use of wood fuel to deforestation leading to greenhouse gas emissions which cause climate change. Despite these concerns, some institutions located in the rural areas of Zambia like boarding schools and colleges still use firewood as a fuel for cooking and heating. Additionally, electricity, where available, is usually based on fossil fuel combustion, and often has high tariffs if connected to the national electricity grid and is also unreliable. On the other hand, biogas produced from animal and other organic wastes has demonstrated to be a cleaner alternative source of energy that can be used for cooking and supply of heat. A case of Nkumbi international college was selected to consider the economic viability of using the animal and agriculture waste from the institutional farm as a feedstock in an anaerobic co-digester to generate biogas for use as fuel for cooking to replace firewood and grid electricity, the current sources of energy for cooking. Results showed that installing a biogas system at the college and using the biogas to replace a combination of firewood and electricity is highly viable with a positive net present value of USD 19,747, a payback period of 3.1 years, and an internal rate of return of 35.5% over a period of 20 years.